ROAD SAFETY PERCEPTION TOWARDS SUSTAINABLE TRANSPORT: A Case of Road Safety Programs in Yogyakarta, Indonesia - NURHIDAYATI, ZUNI ASIH ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The number of fatalities due to traffic accidents to date has reached worrying levels. Thus, various research which concern on road safety programs were actively generated. The aims of this study is suggests a set of scheme on road safety policy improvement in Yogyakarta by firstly understanding the road user perception on current road safety programmes related to road safety problems, then analyse it along with other actor’s role in achieving sustainable transport. “The Five Pillars” as current road safety action plan, officially declared internationally by World Health Organization (WHO), have been conducted in many countries, including Indonesia to actualize safe mobility and “zero accident”. Using Yogyakarta as a case study within the research design, this qualitative study are conducting triangulation technique in data collection which referencing the “The Five Pillars” as standards of quality and verification. Judgement sampling is used for selected participants in several categories (senior high school students, college students and workers) as the subject and victim that mostly involved in road traffic accident. Furthermore, The Theory of Planned Behaviour, Sustainability, Value Creation and Hong Kong’s Transport Policy are several literature that have been used in theoretical part. Based on the results, it indicates there still existed a gap of perception between road users and road safety officer such as police, underlined the irregularities of some programmes implementation. Conclusions, the gap on road safety perception is emerge due to the existence of irregularities within the road safety programs implementation. The role of road user perception are contributed as feedback reccomendation, evaluation for stakeholders in policy implementation and programmes development such as enhancing a walkable city in future. Therefore, a set of improvement on stakeholder coordination, human resource management, public transport, infrastructure, and traffic law enforcement proposed as managerial implication in gaining sustainable transport (social, economic and environmental).